2022
DOI: 10.3390/jfb13030108
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis and In Vivo Fluorescent Bioimaging Application of Eu3+/Gd3+ Co-Doped Fluoroapatite Nanocrystals

Abstract: In this study, Eu3+/Gd3+ co-doped fluoroapatitååe (Eu/Gd:FAP) nanocrystals were synthesized by the hydrothermal method as a fluorescent bioimaging agent. The phase composition, morphology, fluorescence, and biosafety of the resulting samples were characterized. Moreover, the in vivo fluorescent bioimaging application of Eu/Gd:FAP nanocrystals was evaluated in mice with subcutaneously transplanted tumors. The results showed that the Eu/Gd:FAP nanocrystals were short rod-like particles with a size of 59.27 ± 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The nanoparticles not only have smaller sizes but also have good biological activity, as proved by cytotoxicity tests and animal experiments. [66][67][68][69] QYs have always been the focus and difficulty of rare earthdoped nano-fluorescent probes. Researchers 70,71 have found that the doping of RE 3+ into the quantum dot matrix can effectively improve the quantum yield of RE 3+ .…”
Section: Other Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticles not only have smaller sizes but also have good biological activity, as proved by cytotoxicity tests and animal experiments. [66][67][68][69] QYs have always been the focus and difficulty of rare earthdoped nano-fluorescent probes. Researchers 70,71 have found that the doping of RE 3+ into the quantum dot matrix can effectively improve the quantum yield of RE 3+ .…”
Section: Other Substratesmentioning
confidence: 99%
“…The nanoparticles not only have smaller sizes but also have good biological activity, as proved by cytotoxicity tests and animal experiments. 66–69…”
Section: Classification By Matrixmentioning
confidence: 99%